Multidimensional Poverty in Malaysia : Improving Measurement and Policies in the 2020s - Simler, Kenneth; Ali Ahmad, Zainab (World Bank, Washington, DC, 2021)
It has long been recognized that poverty is multidimensional, comprising not only insufficient income but also deprivations in access to basic services, the quality of living conditions, personal security, and other aspects of well-being. Since 2010 there has been rapid growth in the development and use of quantitative measures of multidimensional poverty. This paper analyzes the construction and use of the Multidimensional Poverty Index (MPI) in Malaysia, which the Malaysian government introduced in its national development plan for 2015–2020. It examines avenues for improving the relevance of the MPI in policy discourse by setting deprivation thresholds of the various MPI dimensions (health, education, living conditions, income) at levels more appropriate for an upper-middle-income country such as Malaysia. Recent national survey data are used to estimate the quantitative impact of incrementally adjusting the thresholds of indicators in the current MPI. The potential for new indicators is also explored, drawing from the MPIs used in other middle- and high-income countries. The role of the MPI for informing and monitoring anti-poverty policies is discussed, focusing on unpacking the dimensions of poverty embedded in the MPI, so that policies are better matched to the deprivations observed.